The role of tranexamic acid in the management of postpartum haemorrhage. Issue 3 (December 2022) - Bouthors, Anne-Sophie; Gilliot, Sixtine; Sentilhes, Loïc; Hennart, Benjamin; Jeanpierre, Emmanuelle; Deneux-Tharaux, Catherine; Lebuffe, Gilles; Odou, Pascal
Abstract : In the last decades, tranexamic acid (TXA) has emerged as an essential tool in blood loss management in obstetrics. TXA prophylaxis for postpartum haemorrhage (PPH) has been studied in double-blind, placebo-controlled, randomized clinical trials (RCTs). Given the small observed preventive effect, the systematic use of TXA for vaginal and/or caesarean deliveries remains controversial. The result of a pharmacokinetic modelling suggests that relative to intravenous administration, intramuscular administration may be an equally effective alternative route for preventing PPH and may enable access to this drug in low-resource countries. Prophylaxis is currently studied in high-risk populations, such as women with prepartum anaemia or placenta previa. TXA effectively reduces blood loss and PPH-related morbidity and mortality during active PPH, as demonstrated by high-grade evidence from large RCTs. The drug has a good safety profile: in most cases, only mild gastrointestinal or visual adverse events may be observed. TXA use does not increase the risk of serious adverse events, such as venous or arterial thromboembolism, seizures, or acute kidney injury. The TRACES in vivo analysis of biomarkers of TXA's antifibrinolytic effect have suggested that a dose of at least 1 g is required for the treatment of PPH. The TRACES pharmacokinetic model suggests that because TXA can be lost in the haemorrhaged blood, a second dose should be administered if the PPH continues or if severe coagulopathy occurs. Future pharmacodynamic analyses will focus on the appropriateness of TXA dosing regimens with regard to the intensity of fibrinolysis in catastrophic obstetric events.